2005
DOI: 10.1007/s10482-004-2842-6
|View full text |Cite
|
Sign up to set email alerts
|

Metschnikowia viticola sp. nov., a new yeast species from grape

Abstract: Two yeast strains, producing needle-shaped ascospores under suitable conditions, were isolated from grapes grown in Hungary. Based on these two strains, Metschnikowia viticola (type strain NCAIM Y.01705, CBS 9950, JCM 12561) is proposed as a new yeast species. Considering its phenotypic features, the restriction fragment patterns of 18S rDNA and the sequence of the D1/D2 domain of 26S rDNA, the proposed new species is closely related to Candida kofuensis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 10 publications
(10 reference statements)
0
10
0
1
Order By: Relevance
“…In good agreement with the findings of many other authors (Fleet et al, 2002;Deak, 2007;Barata et al, 2012), H. uvarum was the most abundant species on grapes, which means that on average it gave rise to more colonies per grape sample than any other species. According to several authors a new species belonging to the genus Metschnikowia, M. viticola, was isolated from grapes in Hungary (Peter et al, 2005) and many new species have recently been described in the Metschnikowia pulcherrima clade. These include M. chrysoperlae (Suh et al, 2004), M. fructicola (Kurtzman and Droby, 2001) and M. andauensis (Molnar and Prillinger, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In good agreement with the findings of many other authors (Fleet et al, 2002;Deak, 2007;Barata et al, 2012), H. uvarum was the most abundant species on grapes, which means that on average it gave rise to more colonies per grape sample than any other species. According to several authors a new species belonging to the genus Metschnikowia, M. viticola, was isolated from grapes in Hungary (Peter et al, 2005) and many new species have recently been described in the Metschnikowia pulcherrima clade. These include M. chrysoperlae (Suh et al, 2004), M. fructicola (Kurtzman and Droby, 2001) and M. andauensis (Molnar and Prillinger, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Candida pimensis is identical to M. chrysoperlae for ACT1 and EF2 sequences (Table S5), which could be considered as a suggestion of a possible anamorph/teleomorph relationship, but growth responses and D1/D2 LSU rRNA gene sequences (Suh et al, 2004) do not support taxonomic equivalence. The possibility that Metschnikowia viticola is the teleomorph of C. kofuensis , based on D1/D2 LSU sequences, has been considered but rejected by Péter et al (2005). Their almost identical ACT1 sequences support this connection, but the 54 divergent positions in their RPB2 sequences (Table S5) speak to a different conclusion.…”
Section: Phylogenetic Relationships In the Metschnikowia Cladementioning
confidence: 99%
“…viticola since the species description (Peter et al, 2005) was based on two strains from one grape sample only and the species has been detected only a very few times since then.…”
mentioning
confidence: 99%
“…The species description (Peter et al, 2005) was based on only two strains from a single grape sample. Brezna et al (2010) indicated that the species is present on grapes in the Slovak…”
mentioning
confidence: 99%